ISOLATION OF AGAR DEGRADING BACTERIUM PSEUDOMONAS AERUGINOSA ZSL-2 FROM A MARINE SAMPLE - M. ZIAYODDIN; S. MANOHAR; J. LALITHA (The Bioscan, 2010)
A gram negative bacterium forming orange colonies and designated ZSL-2 was isolated from sea-shore. ZSL-2 was selected for its ability to actively degrade both agar and carrageenans. The cells occurred singly or in pairs as long rods. The temperature range for growth was 20- 40ºC with an optimum at 30ºC, the pH range for growth at 30ºC was from 5.0 to 11, with an optimum around 8.0. The NaCl concentrations required for growth at 30ºC and pH 8.0 ranged from 0 to 5%, with an optimum around 2%. Phylogenetic analysis of 16S rDNA sequences indicated that strain is closely related to Pseudomonas aeruginosa. Based on phenotypic and phylogenetic features the new bacterium designated as Pseudomonas aeruginosa ZSL-2. The bacterium did not utilize other polysaccharides like, alginate, cellulose, xylan and CMC. But utilize agar and carrageenan as sole source of carbon and energy.